Seasonal succession of tabanid species in equine infectious anaemia endemic areas of Italy. Issue 3 (18th February 2019) - De Liberato, C.; Magliano, A.; Autorino, G. L.; Di Domenico, M.; Sala, M.; Baldacchino, F.
Abstract: Equine infectious anaemia (EIA) is a disease with an almost worldwide distribution, with several outbreaks having been reported recently in European countries. In Italy, two regions, Lazio and Abruzzo, are considered as endemic areas for this disease. In nature, the EIA virus is mechanically transmitted by biting flies such as tabanids (Diptera: Tabanidae), although few studies have investigated the epidemiological implications. In the present study, several sites characterized by different levels of EIA prevalence were sampled. In sites with high tabanid populations, a seasonal succession of tabanid species with a dual‐peak corresponding to early active species (i.e. in June to July) and late active species (i.e. in August to September) was clearly observed. Moreover, a positive correlation was found between EIA prevalence and tabanid abundance and species richness, suggesting that tabanid diversity might extend the duration of the seasonal transmission period of EIA. Further observations are required to better assess how vector diversity influence EIA transmission. Abstract : A seasonal succession of tabanid species was observed with a dual‐peak corresponding to early and late active species. Equine infectious anaemia prevalence was positively correlated with tabanid abundance and species richness. Tabanid diversity might extend the duration of the seasonal transmission period of equine infectious anaemia.